An Application of GIS Techniques to Assess the Risk of Disturbance of Archaeological Sites by Mass Movement and Marine Flooding in Auyuittuq National Park Reserve, Nunavut - Solsten, Brenda; Aitken, Alec (Géographie physique et Quaternaire, 2006)
AbstractCoastal regions within Auyuittuq National Park Reserve (ANPR) are sensitive to mass movement processes and threatened by flooding in response to sea level rise. These processes pose a risk to culturally significant archaeological sites within ANPR. Sites at risk of disturbance need to be identified and protected to conserve valuable archaeological resources. Since the costs of identifying and monitoring sites at risk in remote areas are substantial, modern technologies such as Geographic Information Systems (GIS) can be used to create a more rapid and cost-effective means to monitor coastal environments and manage coastal resources. This study examines the application of GIS technology to assess the risk of disturbance of 44 coastal archaeological sites by mass movement and marine flooding within ANPR. Data on surficial materials and slope angles are combined in an overlay analysis to assess terrain sensitivity to mass movement. The output from this analysis is a coarse regional assessment of mass movement potential as it relates to the strength of materials on slopes. The overall risk of disturbance for archaeological sites within ANPR is assessed by combining the risk of mass movement and the risk of marine flooding. Twenty-eight sites within ANPR are identified as being at considerable risk to disturbance: these sites are located largely on glaciomarine sediments at moderate or high slope angles and are at substantial risk to flooding (less than two metres above sea level).